Setting up a National Research Data Curation Service for Qatar: Challenges and Opportunities - Arif Shaon (13761784) (2023)
Over the past decade, Qatar has been making considerable progress towards developing a sustainable research culture for the nation. The main driver behind Qatar’s progress in research and innovation is Qatar Foundation for Education, Science, and Community Development (QF), a private, non-profit organization that aims to utilise research as a catalyst for expanding, diversifying and improving the country’s economy, health and environment. While this has resulted in a significant growth in the number of research publications produced by Qatari researchers in recent years, a nationally co-ordinated approach is needed to address some of the emerging but increasingly important aspects of research data curation, such as management and publication of research data as important outputs, and their long-term digital preservation. Qatar National Library (QNL), launched in November 2012 under the umbrella of QF, aims to establish itself as a centre of excellence in Qatar for research data management, curation and publishing to address the research data-related needs of Qatari researchers and academics. This paper describes QNL’s approach towards establishing a national research data curation service for Qatar, highlighting the associated opportunities and key challenges. Other Information Published in: International Journal of Digital Curation License: http://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.2218/ijdc.v12i2.515